Scientific-practical and legal problems of implementation of the personalized medicine - Bezdieniezhnykh, N.O.; Reznikova, V.V.; Rossylna, O.V. (Experimental Oncology, 2017)
The article is devoted to the comprehensive analysis of scientific, practical and legal issues of personalized medicine that is a rapidly developing science-driven approach to healthcare. It is concluded that there is lack of general legal framework for the encouragement of scientific researches and practical implementation in this field. The article shows foreign experience and prospects for the introduction of personalized medicine as a key concept of healthcare system, which is based on a selection of diagnostic, therapeutic and preventive measures that would be the most effective for a particular person in view of individual characteristics. The conclusions and proposals to improve the current legislation and development of personalized medicine in Ukraine are suggested.